Kehilangan Keluarga Akibat Covid-19 - Sifa Fauziah; Nita Sarlytta Atmaja (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Families who have lost due to Covid-19 experience prolonged grief which will have an impact on psychological problems such as depression, anxiety, and sadness. This study aims to explore the life experiences of families who have experienced loss due to Covid-19. This study used a qualitative method with a phenomenological approach. The participants in this study were 6 people who had experiences of loss due to Covid-19. Family experiences were explored through in-depth interviews and analyzed using the Colaizzi method. The results of this study provide an overview of the experiences of families who have experienced loss due to Covid-19. Families experience unpreparedness to lose due to Covid-19 which is described in four themes, namely a bad death, the family's response to loss, support in the family, and praying for peace of mind. It was concluded that families who experienced loss due to Covid-19 experienced unfinished grief such as a lack of family readiness to accept the loss and not following the rituals that are usually carried out after the loss.Keywords: Covid-19; loss of family; mourn; experience ABSTRAK Keluarga yang kehilangan akibat Covid-19 mengalami duka berkepanjangan yang nantinya berdampak pada masalah psikologis seperti depresi, kecemasan, dan kesedihan. Penelitian ini bertujuan untuk mengeksplorasi pengalaman hidup keluarga yang mengalami kehilangan akibat Covid-19. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Partisipan dalam penelitian ini adalah 6 orang yang mempunyai pengalaman kehilangan akibat Covid-19. Pengalaman keluarga digali melalui wawancara mendalam lau dianalisis menggunakan metode Colaizzi. Hasil penelitian ini memberikan gambaran mengenai pengalaman keluarga yang mengalami kehilangan akibat Covid-19. Keluarga mengalami ketidaksiapan kehilangan akibat Covid-19 yang digambarkan dalam empat tema yaitu kematian yang buruk, respon keluarga terhadap kehilangan, dukungan dalam keluarga, dan berdoa membuat ketenangan hati. Disimpulkan bahwa keluarga yang mengalami kehilangan akibat Covid-19 mengalami duka yang belum selesai seperti kurangnya kesiapan keluarga menerima kehilangan dan tidak mengikuti ritual yang biasanya dilakukan setelah kehilangan.Kata kunci: Covid-19; kehilangan keluarga; berduka; pengalaman